2015
DOI: 10.1093/mnras/stv2211
|View full text |Cite
|
Sign up to set email alerts
|

Galaxy cluster lensing masses in modified lensing potentials

Abstract: Additional information: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.P… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 143 publications
1
41
1
Order By: Relevance
“…Any potential time-evolution of α over this range will be negligible, although we note that more detailed modelling may be required if a sample of useful clusters at redshifts z ≫ 0.1 were to be found. Previous studies have consistently found that the properties of halos are largely unmodified in galileon cosmologies (Barreira et al 2014b(Barreira et al , 2015, especially inside the Vainshtein radius. Outside, at distances larger than ∼ 2 Mpc, more detailed modelling may be required, although M 87, which we consider below, lies well within the Vainshtein radius of the Virgo cluster so this is not a caveat to the results we obtain here.…”
Section: Galaxy Clustersmentioning
confidence: 89%
“…Any potential time-evolution of α over this range will be negligible, although we note that more detailed modelling may be required if a sample of useful clusters at redshifts z ≫ 0.1 were to be found. Previous studies have consistently found that the properties of halos are largely unmodified in galileon cosmologies (Barreira et al 2014b(Barreira et al , 2015, especially inside the Vainshtein radius. Outside, at distances larger than ∼ 2 Mpc, more detailed modelling may be required, although M 87, which we consider below, lies well within the Vainshtein radius of the Virgo cluster so this is not a caveat to the results we obtain here.…”
Section: Galaxy Clustersmentioning
confidence: 89%
“…(6) the "RR" model. Further work on the RR and RT models has been presented in [51][52][53][54][55][56][57][58][59].…”
Section: An Overview Of Nonlocal Modelsmentioning
confidence: 99%
“…Many different approaches have been used to calculate E-mail: manolo@roe.ac.uk cluster masses; taking advantage of clusters acting as gravitational lenses (eg., Kneib 2008, Applegate et al 2014, Barreira et al 2015, Gonzalez et al 2015, using the SunyaevZeldovich effect (eg. Sunyaev & Zeldovich 1970, Birkinshaw & Lancaster 2008, Olamaie, Hobson & Grainge 2013, Churazov, Vikhlinin & Sunyaev 2015, assuming hydrostatic equilibrium and calculating the intracluster medium (ICM) temperature from their X-ray emission (eg., Sarazin 2008, Martino et al 2014, Nelson et al 2014 or using the clusters' galaxy member velocities and assuming dynamical equilibrium (eg., Saro et al 2013, Sifón et al 2013, Tempel et al 2014 or not (eg., Diaferio & Geller 1997, Diaferio 1999).…”
Section: Introductionmentioning
confidence: 99%